IDENTIFICATION OF TEUNGKU CHIK MUHAMMAD AMIN'S LEGACY - Yanti Dewi; Marduati (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
Teungku Chik Muhammad Amin is a scholar from Aceh who is descended from South Yemen's Arab community. Along with promoting society's understanding of Islam and the fight against Dutch forces, he is a person who is quite tenacious. This study's objectives were to learn more about Teungku Chik Muhammad Amin's life, identify his remains, and assess their state of preservation. The explicative (explanatory) or descriptive methods used in this study give a general overview of the archaeological data discovered in terms of time, form, and space as well as demonstrating the correlation between various research variables. In Meunasah Mancang Village, Tiro Truseb District, Pidie Regency, data were gathered by direct observation, interviews, literature reviews, and documentation. Aspects of the data's morphology, technology, and stylistic composition were characterized and examined. The identification has revealed various Teungku Chik Muhammad Amin relics, including Zawiyah Cut, a study hall, an old pond or ablution site, and an old well. Teungku Chik Muhammad Amin's remains have similarly gotten less attention from the parties involved, as seen by their current state. The government of Pidie Regency and other relevant parties are urged to be able to preserve this historical legacy as the cultural heritage of the Acehnese people.